Study of Lymphedema Risk Factors among Patients with Invasive Breast Cancer after the Initial Treatment - Moghadam, Shiva; Saedi, Hamid; Taghizadeh Kermani, Ali; Afzal Aghaee, Monavar; Mottaghi, Taher (Reports of Radiotherapy and Oncology, 2025)
Introduction: Upper limbs lymphedema is one of the rather common and debilitating sequels of breast cancer treatment. The incidence of this sequel has been reported in different sources to be from 25% to 38%. The purpose of this study was to evaluate the incidence and the risk factors of lymphedema following invasive breast carcinoma treatment. Materials and Methods: Recorded data of breast cancer patients referred to Mashhad Omid Hospital between 1997 and 2005 were evaluated for the incidence and risk factors of lymphedema. Univariate and multivariate analysis were performed to evaluate the risk factors using a logistic regression model. Results: Out of 312 patients entering the study 101 patients (32.4%, 95% CI: 27.2-37.6) developed lymphedema. Univariate analysis did not show a statistically significant difference between the rates of lymphedema in radical mastectomy when compared to other types of surgery such as lumpectomy with axillary dissection. Obesity according to body mass index significantly affected the development of lymphedema (p=0.03). The average number of metastatic nodes was 4.56±4.05 in patients who had and 2.48±3.19 in patients who did not have lymphedema (p<0.01). The average percentage of metastatic to excised nodes was %54.59%±37.48 in patients who had and %34.67%±34.84 in patients who did not have lymphedema (p<0.01). Age, the number of excised nodes, the stage of disease, hormonal therapy, adjuvant radiation therapy and chemotherapy had no correlations with lymphedema. Conclusion: According to our findings, body mass index, the number of metastatic nodes and thepercentage of metastatic to excised nodes were correlated with the development of lymphedema.